Judicial Law in Cases Concerning Granting the Right to a Nursing Benefit - Knysiak-Sudyka, Hanna (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
A type of family benefits are, in particular, care benefits, and one of them is the nursing benefit, which has become very attractive in recent years, among others due to its amount. The legal regulation of the institution of the right to nursing benefits raises numerous interpretation doubts and therefore constitutes an excellent field for creating “judge’s law”. The nursing benefit is intended to replace the income resulting from employment which the person caring for the disabled person cannot take up or from which one is forced to resign due to the care provided. However, this benefit is not dedicated to every actual carer of a disabled person, therefore it is extremely important to correctly identify the circle of its potential beneficiaries. Interpretation doubts are also raised by the regulation stating that one of the negative conditions for granting the right to the nursing benefit is the fact that the person providing care has an established right to a retirement. Judicial law-making in cases for granting the right to nursing benefits plays an enormous role that cannot be underestimated.